Pendampingan Branding dan Digital Marketing Pada UMKM Kelurahan Tlumpu, Kota Blitar - Raganta Deyantara; Zawawi Zawawi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The number of businesses that meet the criteria for Micro, Small and Medium Enterprises (MSMEs) in the Tlumpu Village, Blitar City do not yet have clear branding and digital marketing for various reasons. Even though this business has a good impact on the surrounding area. Having a logo that is still old school and unattractive is also the main factor in this business not being able to develop quickly. The methods used in this service activity are surveys, interviews, discussions, and application. The results obtained from this activity are making a new logo, new packaging and creating social media accounts and providing branding and digital marketing insights by providing material for socialization, so that MSME actors in the Tlumpu Village have new insights into the importance of this.